2020
DOI: 10.1038/s41598-020-70786-5
|View full text |Cite
|
Sign up to set email alerts
|

Multi-omic single cell analysis resolves novel stromal cell populations in healthy and diseased human tendon

Abstract: Tendinopathy accounts for over 30% of primary care consultations and represents a growing healthcare challenge in an active and increasingly ageing population. Recognising critical cells involved in tendinopathy is essential in developing therapeutics to meet this challenge. Tendon cells are heterogenous and sparsely distributed in a dense collagen matrix; limiting previous methods to investigate cell characteristics ex vivo. We applied next generation CITE-sequencing; combining surface proteomics with in-dept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
113
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(146 citation statements)
references
References 35 publications
(41 reference statements)
11
113
0
Order By: Relevance
“…Among them, many markers are shared by endothelial cells and fibroblasts. For example, the highly expressed marker Ccl4 in the 7 population has been reported to play an important role in the differentiation of endothelial cells, and collagen Col1a1 is considered to be the marker of endothelial cells ( 47 ). Gpihbp1 ( 48 ), Egfl7 ( 49 ), and Plvap ( 50 ) in the eight groups are also considered to be important markers of endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, many markers are shared by endothelial cells and fibroblasts. For example, the highly expressed marker Ccl4 in the 7 population has been reported to play an important role in the differentiation of endothelial cells, and collagen Col1a1 is considered to be the marker of endothelial cells ( 47 ). Gpihbp1 ( 48 ), Egfl7 ( 49 ), and Plvap ( 50 ) in the eight groups are also considered to be important markers of endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…While many studies have examined the potential of using various stem cell populations to promote healing, originating from both tendon intrinsic ( Walia and Huang, 2019 ) and extrinsic sources ( Costa-Almeida et al, 2019 ), little focus has been directed toward defining the functions and therapeutic potential of tendon cells during tendon healing following an acute injury. Tendon cells are increasingly recognized as a heterogenous population of cells where many, but not all, express the gene Scleraxis ( Scx ) ( Best and Loiselle, 2019 ; Kendal et al, 2020 ; De Micheli et al, 2020 ). Understanding the localization and function of tendon cell subpopulations during healing is likely to be instrumental in better defining the mechanisms that promote scar-mediated healing, which results in poor patient outcomes, and could therefore be used to develop pro-regenerative approaches to improve healing.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Xu et al, have reported a P75 (p75 neurotrophin receptor) expressing cell subpopulation with stem cell characteristics within the perivascular regions which could proliferate within the peritenon and migrate to interstitial space in response to injury ( Xu et al, 2015 ). Finally, single-cell surface proteomics identified a perivascular niche where a tendon cell cluster expressed high levels of CD90 and CD146 ( Kendal et al, 2020 ). Taken together, these results support the perivascular areas as a tendon stem cell niche.…”
Section: Subpopulations Of Tspcsmentioning
confidence: 99%
“…In tendon tissues, clusters of ITGA7 + cells, which are highly similar to those smooth muscle-mesenchymal cells found in muscle are situated around vessels and they also express surface markers CD90 and CD146 ( Giordani et al, 2019 ; Kendal et al, 2020 ). Actually, developmental evidence suggests that TGFβ signaling emanating from muscles and cartilage are critical for tendon progenitors recruitment, implicating the cross-talk between different tissues of the musculoskeletal system ( Pryce et al, 2009 ).…”
Section: Subpopulations Of Tspcsmentioning
confidence: 99%